Software educativo y su fortalecimiento en el aprendizaje significativo de lengua y literatura a estudiantes de bachillerato de la unidad educativa particular Ecomundo, cantón Babahoyo, Provincia los Ríos. - Morejon Villamar, Carlos Julio (2017)
This research paper aims to analyze the educational software in meaningful learning of language and literature to high school students in the special education unit Ecomundo canton Babahoyo Los Rios province, strengthen the work to achieve both the teacher and the student inside and outside the classroom. During the survey to 75 students and 8 teachers, in order to verify the hypothesis in which it was observed that in the organization of the institution you choose to take traditional classes where teaching with educational software is decreased. Teachers are recommended educational software that are established as a tool to support teaching created thinking in the teaching of teaching in which you have to be trained as it is a requirement of today's society where students are the main protagonists of their learning with the need to increase the development of meaningful learning of high school students still need to increase teachers new teaching strategies.